ANALISIS PERUBAHAN DAERAH POTENSI IKAN MENGGUNAKAN CITRA SATELIT MODIS LEVEL 1B (STUDI KASUS : SELAT BALI) - Sukojo, Bangun Muljo; Zahroh, Latifatul (Departemen Teknik Geomatika ITS, 2017)
Bali Stait is a fishery potential strait which located between Java and Bali Island. Bali Strait has much nutriens, which the nutrients are source of food for fish, because the influence of Java Sea and Indian Ocean. Remote sensing technology is used to make maps of fishery potential areas to optimalize the fishery potential of Bali Strait. On this research, fishery potential area is identified by some parameters. The parameters are 0.2 mg/L – 1 mg/L concentration of chlorophyll-a, 20ºC - 30ºC sea surface temperature and having >= 0.5ºC front thermal. The parameters are obtained from data processing of MODIS satellite imagery. OC3M algoritm is used to process concentration of chlorophyll-a meanwhile sea surface temperature (SPL) is precessed by Minnet algoritm (2001). The overlay results of both parameters are used to identify front thermal based on 4km x 4km sized fishing net (fishnet). The results of the research indicate that the greatest number of fishery potential areas are happened on April 2012 which the numbers are about 45 fishery potential areas. Significant decreasing of fishery potential areas is happened on October 2012 with only one remaining area of fishery potential. On May 2013 fishery potential areas increase to 22 areas. The results show that Bali strait has more fishery potential areas on April and May than October.